Biofuel in Ghana: Potentials and strategies for policy implementation - Stephen Kelly Kissi; Wilson Ofori Sarkodie; Mohammed Takase; Emmanuel Amankwah (Fuel Communications)
Africa has a pressing need for biofuel policies due to several interconnected challenges encompassing vulnerability to price fluctuations, rural development, waste and land use management, and the need for value-added agricultural goods. State biofuel policies contribute to the ongoing global discourse on climate change, green and circular economy, and sustainability. Unfortunately, the resource curse seems to have befallen the Ghanaian economy as the nation still imports petroleum products after discovering enormous oil reserves. This article reviews Ghana's current biomass potential drawing lessons from failed projects and initiatives of top biofuel nations to effectively implement Ghana's latest biofuel policy. A significant portion of land in Ghana remains unused, yet utilizing less than 3 % of this land would be sufficient to meet the B10/E10 biofuel target using cassava as the feedstock. A closer examination of successful biofuel initiatives in Brazil and the United States highlights common factors contributing to their achievements. These include ambitious blending mandates, substantial investments in infrastructure, technology, and research, active stakeholder participation, and the provision of fiscal incentives. While Ghana's Renewable Energy Master Plan incorporates some of these components, its current targets lack sufficient ambition. Addressing these gaps in practice could place Ghana on a trajectory toward becoming one of the world's leading biofuel producers.